Pelatihan Pembuatan Media Promosi Kesehatan Digital Bagi Pegawai Puskesmas Untuk Meningkatkan Kompetensi Edukasi Kesehatan Masyarakat - Suhari Suhari; Zamli Zamli (-, 2026)
The use of digital health promotion media in community health centers remains limited due to the inadequate capacity of health workers to develop educational materials that are attractive, informative, and easy for the public to understand. This community service program aimed to enhance the knowledge and skills of staff at UPTD Puskesmas Polara in developing digital health promotion media. The program involved 10 participants and was conducted through lectures, demonstrations of graphic design applications, hands-on practice, mentoring, and performance evaluation. Participants were assessed based on their ability to produce digital health promotion materials that met health communication principles. The results showed that 8 participants (80%) achieved competence in creating digital posters and health infographics, while 2 participants (20%) required further mentoring. In addition to improving participants’ competencies, the program produced various digital health promotion materials that are ready to be used in community health education activities. Practice-based training combined with continuous mentoring proved effective in strengthening the capacity of community health center staff and supporting promotive and preventive health programs through the effective use of digital technology.